2015
DOI: 10.1590/1517-86922015210101578
|View full text |Cite
|
Sign up to set email alerts
|

Imersão em água fria não acelerou a recuperação após uma partida de futsal

Abstract: Introduction: cold-water immersion (CWI) is a popular recovery strategy; however, there is limited evidence of the effectiveness of this method in sport settings. Objective: to investigate the effect of CWI on muscle soreness and anaerobic performance after a Futsal match. Methods: ten players performed two simulated matches followed by two randomized recovery conditions (CWI or passive rest -C), separated for seven days. During the recovery interventions, the players remained seated in a comfortable position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
(46 reference statements)
0
1
0
1
Order By: Relevance
“…In addition, a busy Futsal match schedule with short rest periods can affect the decrease in physical performance and fatigue in futsal players. Several studies have shown that after one match, futsal players experience a decrease in anaerobic performance (Moreira et al, 2015), lower body's muscle power, decreased running performance and neuromuscular variables (Miloni et al, 2016), a decrease in average pulse, heart rate maximum pulse, and high-intensity running distance when the match began to appear in the second half (Milioni et al 2016). It shows that futsal causes tiredness (fatigue) and indicating a decrease in physical performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a busy Futsal match schedule with short rest periods can affect the decrease in physical performance and fatigue in futsal players. Several studies have shown that after one match, futsal players experience a decrease in anaerobic performance (Moreira et al, 2015), lower body's muscle power, decreased running performance and neuromuscular variables (Miloni et al, 2016), a decrease in average pulse, heart rate maximum pulse, and high-intensity running distance when the match began to appear in the second half (Milioni et al 2016). It shows that futsal causes tiredness (fatigue) and indicating a decrease in physical performance.…”
Section: Introductionmentioning
confidence: 99%
“…verificaram os efeitos da crioterapia por meio do SJ antes em atletas profissionais de voleibol, percebeu-se que a crioterapia de imersão foi ineficiente para a melhora no desempenho. De forma adicionalMoreira et al (2015) investigaram os efeitos da crioterapia na recuperação das capacidades de força e potência em atletas profissionais de futsal por meio do CMJ, e da mesma forma que neste estudo não houve diferença entre grupos e momentos.…”
unclassified